Malaysia business (MNCs) (Singapore : Now2Market, 2003)
Summary: A marketing tool which is providing the latest updated information and help company to generate leads, establish contact and reduce expenses by Telemarketing, Direct mailing, Fax broadcast, Fax merge Broadcast, SMS messaging, SMS chat communicaiton, Phone advertisement and personalized e-mail marketing
System requirements : Microsoft Windows 98SE/ME/XP/2000; Intel pentium III 500Mhz; 128MB RAM Memory; 8X CD-ROm; 500MB hard disk space; 800 X 600 video card; Moderm-Group 3 Class 1/2 Moderm (fax broadcast); World program (such as MMsWord-mail merge); Email program (such as MS Outlook-export emails); SMS program (GSM moderm/mobile phone); Phone ads ( microphone/sound/cart/speakers)
Keywords: Business networks -- Malaysia; Marketing -- Malaysia -- Communication system